2022
DOI: 10.3390/ijms23042381
|View full text |Cite
|
Sign up to set email alerts
|

Common Molecular Targets of a Quinolone Based Bumped Kinase Inhibitor in Neospora caninum and Danio rerio

Abstract: Neospora caninum is an apicomplexan parasite closely related to Toxoplasma gondii, and causes abortions, stillbirths and/or fetal malformations in livestock. Target-based drug development has led to the synthesis of calcium-dependent protein kinase 1 inhibitors, collectively named bumped kinase inhibitors (BKIs). Previous studies have shown that several BKIs have excellent efficacy against neosporosis in vitro and in vivo. However, several members of this class of compounds impair fertility in pregnant mouse m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Then, the columns were separated, and the binding proteins were eluted with 50 mM acetic acid (5 mL per column). The eluates were lyophilized and stored at −80 °C [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the columns were separated, and the binding proteins were eluted with 50 mM acetic acid (5 mL per column). The eluates were lyophilized and stored at −80 °C [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In earlier studies, we have successfully identified common targets of thiazolides, a class of broad anti-infective and anti-cancer drugs, in protozoan parasites [ 10 , 11 ], as well as host cells [ 12 , 13 ], by affinity chromatography, followed by gel electrophoresis and the identification of major bands by mass spectrometry (MS). In recent studies [ 14 , 15 ], we have alleviated the limitations of this method by subjecting cell-free extracts from parasites and suitable host cells to differential affinity chromatography (DAC) coupled to MS. This approach allows the identification of entire proteomes binding to compounds of interest but not to (closely related) ineffective compounds and not to single proteins anymore [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Differential affinity chromatography (DAC) Differential affinity chromatography was performed similarly as described previously (Anghel et al, 2021;Müller et al, 2022aMüller et al, , 2022b. Parasite extracts were passed first through a mock column (Küster et al, 2015) followed by a column containing effective or ineffective drugs and at a flow rate of 0.25 ml/min.…”
Section: (B) Metacestode Protein Extraction For Affinity Chromatographymentioning
confidence: 99%
“…Differential affinity chromatography (DAC) is based on pull-downs of cell free extracts on columns coated with effective compounds or ineffective derivatives followed by nano-liquid chromatography coupled to tandem mass spectrometry (nLC-MS/MS) of the eluates. In recent studies, DAC has been used to identify molecular targets of ruthenium complexes in Toxoplasma gondii and Trypanosoma brucei ( Anghel et al, 2021 ), and to identify molecular targets of a bumped kinase inhibitor in Neospora caninum and Danio rerio ( Müller et al, 2022a ) and proteins binding to Leucinostatin-like peptides ( Müller et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%